Endoport-assisted surgical evacuation of a deep-seated cerebral abscess. (July 2018) - Moosa, Shayan; Ding, Dale; Mastorakos, Panagiotis; Sheehan, Jason P.; Liu, Kenneth C.; Starke, Robert M.
Highlights: Deep-seated intracranial abscesses can be challenging to treat surgically. An endoport improves accessibility and safety in surgical treatment of abscesses. This is the first account of endoport-assisted evacuation of a cerebral abscess. Abstract: Conventional surgical treatment for cerebral abscesses includes craniotomy or stereotactic aspiration. Deep-seated, large abscesses pose a challenge to neurosurgeons, due to the risk of injury to the cortex and white matter tracts secondary to the brain retraction necessary to access the lesion. The endoport is a tubular conduit that can be employed for minimally invasive approaches to deep-seated intracranial lesions, and it may reduce the length of dural opening, size of corticotomy, and retraction-related injury. In this technical note, we present the first report of an adult with a deep cerebral abscess which was successfully treated with endoport-assisted surgical evacuation. The endoport has been shown to be useful for the treatment of other intracranial pathologies, and we believe that this technology may be employed for the evacuation of appropriately selected cerebral abscesses.